Solid Answers: America's Foremost Family Counselor Responds to Tough Questions Facing Today's Families - James Dobson 1936- (USA Tyndale House Publishers, Inc., 1997)
America's foremost family counselor responds to tough questions facing today's families.
Understanding the nature of children -- Raising the preschool child -- Disciplining the preschool child -- Children's health and well-being -- Attention deficit disorder in children and adults -- Effective parenting today -- Disciplining the elementary school child -- To spank or not to spank -- What's a mother to do? -- Education : public, private, and home schooling -- Sex education : where, when, and how -- Spiritual life of the family -- The tougher spiritual questions -- Sibling rivalry -- Help for single parents and stepparents -- Living with a teenager -- The delicate art of letting go -- Advice to young adults -- Building self-confidence in children and teens -- Making marriage work -- Money matters -- Families under fire -- The great marriage killers -- The sanctity of life -- Other issues facing the family -- Principles and concepts drawn from Dr. Dobson's books and statements through the years.
Keywords: Philosophy and Psychology (3GdadSaI hYde GdfaSs; Child rearing -- Religious aspects -- Christianity -- Miscellanea; Child rearing -- United States -- Miscellanea; Families -- Religious aspects -- Christianity -- Miscellanea; Families -- Religious life -- United States -- Miscellanea; General